Genomic Essentialism: Its Provenance and Trajectory as an Anticipatory Ethical Concern - Sabatello, Maya (The Hastings Center report, 2019)
Since the inception of large-scale human genome research, there has been much caution about the risks of exacerbating a number of socially dangerous attitudes linked to human genetics. These attitudes are usually labeled with one of a family of genetic or genomic “isms” or “ations” such as “genetic essentialism,” “genetic determinism,” “genetic reductionism,” “geneticization,” “genetic stigmatization,” and “genetic discrimination.” The psychosocial processes these terms refer to are taken to exacerbate several ills that are similarly labeled, from medical racism and psychological fatalism to economic exploitation and social exclusion. But as genomic information becomes more familiar in clinical and research settings as well as other life activities, do we need to continue to worry so much about this family of attitudes and their impact on existing problems? In genomics, the underlying anxiety has been that disclosure of genomic information will trigger a series of (seemingly unavoidable) negative responses that will affect individuals, their families, and their communities at large. The fundamental social challenges that hyperbolic genomic messaging, low genomic literacy, and “folk biology” help sustain remain to be addressed. If we hope to break the cycle of genomic isms and ations, we will have to get better at resisting overinterpretations of the relevance that genomics has for people’s future potentials, ancestral vulnerabilities, community memberships, and ethnic affiliations.